Efficient direct regeneration of true-to-type Pogostemon cablin benth from leaf explant and profile of essential oils - Sita Fitriana, (2011)
Pogostemon cablin Benth is one of the best patchouli species, which has huge potential to serve the cosmetic and pharmaceutical industries due to its fragrance and aromatic essential oils. The purpose of the present study is to establish an efficient and reproducible protocol for direct multiple shoot induction from patchouli leaves with clonal fidelity of the desired cultivar. Shoot induction from leaf culture of patchouli was tested on Murashige and Skoog (MS) basal medium supplemented with 2.26 μM 2,4-D (Dichlorophenoxyacetic acid) and Benzylaminopurine (BAP) at 0, 1.11, 2.22, 3.33, 4.44 μM. The highest frequency of shoot induction (88 %) and number of shoots per explant (102) was observed on solid MS medium supplemented with 3.33 μM of BAP. The addition of 2,4-D did not favour shoot induction but induced callus formation. For elongation of shoots, MS basal medium gave a better response compared to halfstrength MS medium and the average length of shoot was 3.3 cm. Elongated shoots gave good rooting on MS basal liquid medium with an average of 12 roots per shoot, with an average length of 2.75 cm. The regenerated tissue cultured plantlets were acclimatized and successfully established in soil (90%). Genetic fidelity of the tissue cultured plants was assessed using the technique of Random Amplified Polymorphic DNA (RAPD). Nine arbitrary decamers displayed same banding profile in all the tissue cultured plants and in mother plant. The molecular analysis confirmed the true-to-type nature of the tissue cultured plantlets.The profile of essential oils determined by gas chromatography / mass spectrometry in tissue cultured plants and mother plants showed similar patterns. However, the levels of major essential oils were higher in all tissue cultured plants characterized. This study provides the pre-requisite to improve the traits of the desired cultivar of patchouli by genetic transformation in the future.